Model relating superconductive penetration depth and metallurgical phase separation in amorphous La70 Cu30 - Arce, R. O.; Cruz, Francisco de la; Fink, H. J. (Pergamon Press, 1982)
Fil: Arce, R. O. Comisión Nacional de Energía Atómica; Argentina